(untitled) (Global Journal of Science Frontier Research, 2017)
This paper treats the concept of the Gaussian probability distribution both for the target and observer. The resulting observations become Gaussian distributions as well. The time coordinate gets an equal setting as any physical quantity. This treatment is purely classical with no essential reference to quantum mechanics nor to theory of relativity.